Follow-up of pseudomembranous colitis in children using colonoscopy - Ahadi, Parisa; Mardi, Ali (International Journal of Contemporary Pediatrics, 2024)
Pseudomembranous colitis (PC) is a common nosocomial disease. The most common etiology of the disease is Clostridium difficile and also many other causes can be having role in the occurrence of the disease. This disease is not very common in children and is mostly related to the use of antibiotics and hospitalization. Here, we report a case of PC in an 8-year-old boy who had no history of taking antibiotics and hospitalization.